Indanone-based two-dimensional covalent organic framework material, preparation method and application of truxene-based two-dimensional covalent organic framework material as lithium ion battery positive electrode material

The existing COFs materials are solved by using tripolyvinyl-based two-dimensional covalent organic frame material (TRO-BT-COF) and using high connectivity building blocks of 3-connected planar ligands to form a fully conjugated single crystal structure. In the problems of low actual specific capacity and insufficient cycle stability in the positive electrode materials of lithium-ion batteries, efficient electrochemical performance is achieved.

CN119409915AActive Publication Date: 2025-02-11NANKAI UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411535179.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-11
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

The existing two-dimensional covalent organic frame materials (COFs) are not very specific in the application of lithium-ion battery positive electrode materials, and the cycle stability and active site utilization need to be improved.

Method used

Using tripolyinone-based two-dimensional covalent organic framework material (TRO-BT-COF), a highly connected building block of 3-connected planar ligands is formed to form a fully conjugated single crystal structure, which is rich in electrochemical activity. The yoke carbonyl and carbon-nitrogen double bond promotes uniform distribution and full exposure of redox active sites.

Benefits of technology

It achieves high reversible specific capacity, excellent cycle stability and rate performance, significantly improving the practical application performance of COFs materials in the positive electrode materials of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409915A_ABST
    Figure CN119409915A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of lithium ion battery organic positive electrode materials, and particularly relates to a truxene two-dimensional covalent organic framework material, a preparation method and application of the truxene two-dimensional covalent organic framework material as a lithium ion battery positive electrode material. The truxene ketone-based two-dimensional covalent organic framework material prepared by the invention has a full-conjugated single-crystal structure, is rich in a large number of conjugated carbonyl groups and carbon-nitrogen double bonds with electrochemical activity, can provide high-density oxidation-reduction active sites, and shows high reversible specific capacity when being used as an electrode active material in a lithium ion battery; and the material has excellent cycling stability and rate capability, and has potential application value in the aspect of organic electrode materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of organic positive electrode materials for lithium ion batteries, and specifically relates to a trimerized indenone-based two-dimensional covalent organic framework material, a preparation method and an application thereof as a positive electrode material for lithium ion batteries. Background Art

[0002] As a power source, lithium-ion batteries (LIBs) have been successfully and widely used in portable electronic devices and electric vehicles. However, with the advancement of technological development, they face two core challenges: first, the improvement of energy density has encountered a bottleneck, which limits the endurance; second, the dependence on transition metals such as cobalt and nickel in inorganic cathode materials has caused concerns about resource scarcity and resource sustainability. Organic cathode materials (OCMs) have gradually become a research hotspot due to their significant potential in electrochemical performance and significant advantages in resource sustainability. Thanks to the rich electroactive groups or units of OCMs and the high designability of organic structures, they are intended to be used in rechargeable lithium batteries and other advanced battery systems in order to break through the limitations of current technologies.

[0003] Covalent organic framework compounds (COFs) are a new class of crystalline organic polymers with inherent porosity, structural periodicity and light element components. They construct covalently connected periodic two-dimensional or three-dimensional extended frameworks through organic units. COFs materials have achieved rapid development due to their diverse structures, high porosity, high chemical stability and high theoretical capacity. Most of the traditional COFs material research focuses on 2D COFs because their layered structure, rich active sites, high porosity and clear channels are conducive to the transfer and deintercalation of charges and lithium ions. However, in practical applications, the actual specific capacity of 2D COFs materials is not ideal. Yang et al. designed and prepared COF-TRO positive electrode materials and used them in all-solid-state organic lithium-ion batteries. The results showed that the reversible specific capacity of COF-TRO reached 268mAh g -1 , almost reaching 97.5% of the theoretical calculated capacity. In addition, COF-TRO has excellent cycle stability (capacity retention rate is 99.9% after 100 cycles at 0.1°C), which shows that COF based on trimerized indenone has great potential in energy storage applications. However, its reversible capacity is not high, and the cycle stability and active site utilization need to be further improved. Therefore, it is necessary to develop conjugated two-dimensional COFs with high actual specific capacity and strong structural stability, as well as to explore high-quality synthesis methods, especially for the application of COFs materials in the field of organic cathode materials for lithium-ion batteries. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide an application of a trimerized indenone-based two-dimensional covalent organic framework material as a positive electrode material for lithium-ion batteries. The prepared trimerized indenone-based two-dimensional covalent organic framework material presents a fully conjugated single crystal structure and is rich in a large number of electrochemically active conjugated carbonyl groups and carbon-nitrogen double bonds, and can provide a high density of redox active sites. As an electrode active material in a lithium-ion battery, it exhibits a high reversible specific capacity, excellent cycle stability and rate performance, and has potential application value in organic electrode materials.

[0005] The purpose of the present invention is achieved by the following technical solutions:

[0006] The first aspect of the present invention provides an application of a tripolyindenone-based two-dimensional covalent organic framework material as a positive electrode material for a lithium-ion battery. The tripolyindenone-based two-dimensional covalent organic framework material (TRO-BT-COF) has a structural formula as shown below:

[0007]

[0008] The second aspect of the present invention is to provide a tri-indenone-based two-dimensional covalent organic framework material (TRO-BT-COF) having the structure as above.

[0009] The third aspect of the present invention is to provide a method for preparing the above-mentioned trimeric indenone-based two-dimensional covalent organic framework material (TRO-BT-COF), comprising the following steps:

[0010] (1) placing indane triamine and trimesic acid aldehyde in a flask at a molar ratio of 1-5:1-5;

[0011] (2) preparing a certain amount of mixed organic solvent, then pouring the powder in step (1) into the prepared mixed solvent, and fully dispersing it by ultrasound;

[0012] (3) adding a certain amount of acidic catalyst to the mixed solution of step (2), and then circulating liquid nitrogen freezing-vacuuming-thawing to degas, and reacting at 130-160° C. for 3-4 days to obtain a suspension;

[0013] (4) After the suspension is cooled to room temperature, the precipitate is collected by filtration, and then washed, purified and vacuum dried to obtain a tri-indenone-based two-dimensional covalent organic framework material (TRO-BT-COF).

[0014] Furthermore, the organic solvent is a high boiling point solvent; the boiling point range is 70-170°C; preferably one or more of mesitylene, 1,4-dioxane, toluene, chlorobenzene, pyridine and cyclohexanone. Further preferably, the organic solvent is a mixture of mesitylene and 1,4-dioxane in a volume ratio of 1:1.

[0015] Further, the acidic catalyst is one or more of acetic acid, trifluoroacetic acid, sulfuric acid, and propionic acid. Preferably, the acidic catalyst is acetic acid with a concentration of 6 mol / L, and the volume ratio of acetic acid to organic solvent is 1:10.

[0016] Furthermore, the washing liquids used in the washing treatment are dichloromethane, ethanol, acetone and tetrahydrofuran in sequence.

[0017] Furthermore, the purification method also includes Soxhlet extraction.

[0018] Furthermore, the drying treatment is vacuum drying at 60-90° C. for 12-30 hours.

[0019] The fourth aspect of the present invention provides a lithium-ion battery positive electrode material, which is the above-mentioned trimerized indenone-based two-dimensional covalent organic framework material.

[0020] The fifth aspect of the present invention provides a positive electrode plate, which is prepared by mixing the trimerized indenone-based two-dimensional covalent organic framework material with conductive carbon and a binder in a mass ratio of 5:4:1.

[0021] The sixth aspect of the present invention provides a lithium-ion battery, wherein the positive electrode is prepared by mixing a tripolyindenone-based two-dimensional covalent organic framework material with a conductive carbon and a binder in a mass ratio of 5:4:1, the matching negative electrode is a lithium sheet, and in the matching electrolyte, the organic solvent is composed of ethylene glycol dimethyl ether and 1,3-dioxolane in a volume ratio of 1:1, and the solute is lithium bistrifluoromethanesulfonyl imide with a concentration of 1 mol / L.

[0022] The invention proposes a method for preparing a lithium ion positive electrode material based on a two-dimensional covalent organic framework 2D COF material with three-connected planar ligands, which can effectively solve the problem that the actual specific capacity of 2D COFs materials in practical applications is not ideal, thereby affecting their electrochemical performance in actual use. The present invention uses two three-connected planar organic ligands, and this highly planar organic monomer can promote the π-π stacking between COFs material molecules, and the formed sheet structure is that the active sites are evenly distributed and fully exposed so that they can be fully utilized, thereby obtaining a COFs material with high crystallinity, high specific capacity and good stability.

[0023] The three-linked trimeric indenone amines and aromatic aldehydes selected in the present invention both have a central π-conjugated planar structure, and the trimeric indenone-based two-dimensional covalent organic framework material formed by the two has a fully conjugated planar configuration, which is conducive to charge transfer and can also maintain the stability of the three-dimensional framework. The two building blocks have a large nitrogen content and a large number of benzene rings, and a large number of evenly distributed imine bonds in the structure, which can provide abundant lithium storage active sites and can be fully utilized while having good stability, thereby obtaining excellent lithium storage performance.

[0024] The present invention focuses on using 2D [3+3] COF materials prepared by Schiff base reaction of 3-linked tri-indenone amine ligands and 3-linked aromatic aldehyde ligands as positive electrode active materials for lithium-ion batteries, exploring the synthesis method of highly crystalline 2D COF through highly connected planar building blocks, promoting the development of COF materials with novel topological structures synthesized using highly connected building blocks, and greatly enriching the types of 2D COFs.

[0025] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0026] (1) The present invention proposes a method for preparing a lithium ion positive electrode material of a trimerized indenone-based two-dimensional covalent organic framework material (TRO-BT-COF) positive electrode material, which can be used as a lithium ion positive electrode material by connecting 3 2D high connectivity building blocks and then synthesizing a two-dimensional topological structure and a highly connected permanent porosity 2D COF through solution heat, and also provides the possibility for enriching 2D COF materials and applying them in various fields.

[0027] (2) The 2D COF lithium-ion battery positive electrode material prepared by the present invention is different from the existing COFs electrode materials that have high theoretical capacity but low actual specific capacity. The new fully conjugated 2D COF material synthesized by the unique planar ligand of the present material has rich active sites evenly distributed, and the fully conjugated planar framework structure has excellent thermal stability and chemical stability, thereby exerting a higher specific capacity.

[0028] (3) The present invention proposes a method for preparing a lithium ion positive electrode material of a trimerized indenone-based two-dimensional covalent organic framework material (TRO-BT-COF) positive electrode material. Compared with the traditional vacuum tube preparation method, this preparation method is simple to synthesize, green and environmentally friendly, low-cost and safer. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The powder X-ray diffraction refined spectrum of the tri-indenone-based two-dimensional covalent organic framework material (TRO-BT-COF) prepared in Example 1 of the present invention;

[0030] Figure 2 The powder X-ray diffraction spectrum of the tripolyindenone-based two-dimensional covalent organic framework material (TRO-BT-COF) prepared in Comparative Examples 1-6 of the present invention;

[0031] Figure 3 The Fourier transform infrared spectrum of the tripolyindenone-based two-dimensional covalent organic framework material (TRO-BT-COF) prepared in Example 1 of the present invention;

[0032] Figure 4The tripolyindenone-based two-dimensional covalent organic framework material (TRO-BT-COF) prepared in Example 1 of the present invention 13 C solid NMR spectrum;

[0033] Figure 5 The nitrogen adsorption-desorption isotherm of the tripolyindenone-based two-dimensional covalent organic framework material (TRO-BT-COF) prepared in Example 1 of the present invention;

[0034] Figure 6 This is a pore size distribution curve of the tripolyindenone-based two-dimensional covalent organic framework material (TRO-BT-COF) prepared in Example 1 of the present invention;

[0035] Figure 7 The high-magnification transmission electron microscopy image and selected area electron diffraction image of the tripolyindenone-based two-dimensional covalent organic framework material (TRO-BT-COF) prepared in Example 1 of the present invention;

[0036] Figure 8 This is a constant current charge-discharge curve diagram (0.2C) of the tripolyindenone-based two-dimensional covalent organic framework material (TRO-BT-COF) prepared in Example 1 of the present invention;

[0037] Fig. 9 Cyclic stability diagram (0.05-0.2C) of the tri-indenone-based two-dimensional covalent organic framework material (TRO-BT-COF) prepared in Example 1 of the present invention;

[0038] Fig.10 This is a rate performance diagram (0.2-3C) of the trimerized indenone-based two-dimensional covalent organic framework material (TRO-BT-COF) prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0039] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0040] The present invention is further described below in conjunction with specific embodiments and drawings.

[0041] Example 1

[0042] The specific preparation steps of a tri-indenone-based two-dimensional covalent organic framework material (TRO-BT-COF) are as follows:

[0043] (1) Add 32 mg of indanone-triamine and 12.16 mg of trimesic acid to a 10 mL flask, then add a mixture of mesitylene and 1,4-dioxane (volume ratio of 0.5 mL:0.5 mL), dissolve under ultrasonication, and then add 0.1 mL of 6 mol / L acetic acid aqueous solution.

[0044] (2) The reaction system was subjected to a degassing treatment by freeze-vacuum-thaw cycles in liquid nitrogen three times, and the reaction mixture was sealed in an oil bath and heated to 150° C. for 3 days while stirring.

[0045] (3) After the reaction is completed, the mixture is cooled to room temperature, and the solid is collected by filtration, and then washed with dichloromethane, ethanol, acetone and tetrahydrofuran. In addition, Soxhlet extraction is performed for 3 days to further purify the product, and finally vacuum dried at 80°C for 24 hours to obtain a dark red powder tri-indenone-based two-dimensional covalent organic framework material (TRO-BT-COF).

[0046] Figure 1 The XRD refinement results show that the theoretical calculation results of AA stacking correspond to the experimental results, proving that the structure of the obtained tri-indenone-based two-dimensional covalent organic framework material (TRO-BT-COF) is indeed as shown in formula (I). The results show that this material exhibits high crystallinity.

[0047] Figure 3 The infrared spectrum of the tripolyindenone-based two-dimensional covalent organic framework material (TRO-BT-COF) shows that the -1 (corresponding to the stretching vibration peak of the C=N group) and 1690 cm -1 There is a characteristic peak at (corresponding to the stretching vibration peak of the C=O group), which proves the formation of an imine bond and the existence of a carbonyl group, indicating that a Schiff base reaction has occurred.

[0048] Figure 4 The tri-indenone-based two-dimensional covalent organic framework (TRO-BT-COF) 13 C solid NMR spectrum, the results show that: NMR carbon spectrum can observe chemical shifts at 152.21 and 190 ppm, indicating the formation of imine bond and the existence of carbonyl group, which once again proves the successful polymerization of the two monomers.

[0049] Figure 5 , Figure 6 The nitrogen adsorption-desorption isotherm and pore size distribution curve of the obtained tripolyindenone-based two-dimensional covalent organic framework material (TRO-BT-COF) are shown. The results show that the obtained tripolyindenone-based two-dimensional covalent organic framework material has a hierarchical porous structure. The specific surface area of ​​the tripolyindenone-based two-dimensional covalent organic framework material (TRO-BT-COF) is 62.1739 m 2 g-1 , the pore size distribution is concentrated at 1.8 nm;

[0050] Figure 7 (a) shows the HRTEM image of the obtained trimeric indenone-based two-dimensional covalent organic framework material (TRO-BT-COF). The results show that the trimeric indenone-based two-dimensional covalent organic framework material (TRO-BT-COF) has a lamellar morphology. Figure 7 (b) shows the selected area electron diffraction pattern of the obtained trimeric indenone-based two-dimensional covalent organic framework material (TRO-BT-COF). The results show that the diffraction points of the trimeric indenone-based two-dimensional covalent organic framework material (TRO-BT-COF) are arranged in an orderly array, proving its single crystal structure.

[0051] Application of the trimerized indenone-based two-dimensional covalent organic framework material (TRO-BT-COF) prepared by the present invention in lithium-ion batteries.

[0052] (1) According to the ratio of active material: conductive carbon: binder = 5:4:1, first weigh 0.025g of DAAQ-TFPCOF powder and 0.02g of Ketjen black (ECP-600JD) into a mortar and grind for 30 minutes. Then pour the ground mixed powder into a polytetrafluoroethylene glass bottle containing 0.005g of powder, and use a medicine spoon to repeatedly knead it into a shiny ball. Roll it into a round piece with a size of 10mm, and evenly roll it onto a titanium mesh with a diameter of 10mm. Dry it at 80℃ under vacuum conditions for more than 12h to fully evaporate the solvent to obtain a positive electrode sheet.

[0053] (2) Assemble the prepared positive electrode sheet in a glove box filled with argon (w(H2O)≤0.1ppm, w(O2)≤0.1ppm): the positive electrode sheet is the working electrode, the high-purity lithium sheet is the counter electrode; Celgard 2400 is the diaphragm; in the electrolyte, the organic solvent is a mixture of ethylene glycol dimethyl ether (DME) and 1,3-dioxolane (DOL) in a volume ratio of DME:DOL=1:1, and the solute is lithium bistrifluoromethanesulfonyl imide (LiTFSI) with a concentration of 1mol / L. CR2032 button cells are assembled under a pressure of 1Mpa. The voltage setting range is 1-3.5V.

[0054] (3) Test conditions

[0055] At room temperature, the battery was left to stand overnight, activated at 0.05C for 50 cycles, and then cycled at 0.2C for 350 cycles for cycle performance test; rate performance tests were carried out at rates of 0.2, 0.5, 1, 2, and 3C, respectively.

[0056] Figure 8The tri-indenone-based two-dimensional covalent organic framework material (TRO-BT-COF) has a capacity of 445 mAh g -1 The discharge specific capacity accounts for 99.1% of the theoretical capacity.

[0057] Fig. 9 It is shown that after 400 cycles, the theoretical capacity retention rate of the battery based on tripolyindenone-based two-dimensional covalent organic framework material (TRO-BT-COF) as the positive electrode material is 84.5%, which has good cycle stability.

[0058] Fig.10 It reflects the rate performance of the battery and proves its excellent rate performance and structural stability.

[0059] Comparative Example 1

[0060] The difference from Example 1 is that the concentration of acetic acid is 5 mol / L.

[0061] Comparative Example 2

[0062] The difference from Example 1 is that the concentration of acetic acid is 7 mol / L.

[0063] Comparative Example 3

[0064] The difference from Example 1 is that step (2) is reacted at 120° C. for 3 days.

[0065] Comparative Example 4

[0066] The difference from Example 1 is that step (2) is carried out at 170° C. for 3 days.

[0067] Comparative Example 5

[0068] The difference from Example 1 is that step (2) is carried out at 150° C. for 2 days.

[0069] Comparative Example 6

[0070] The difference from Example 1 is that step (2) is carried out at 150° C. for 5 days.

[0071] Figure 2 The XRD comparison diagram of the trimerized indenone-based two-dimensional covalent organic framework material (TRO-BT-COF) obtained under different experimental conditions is shown. By adjusting the concentration of the acetic acid solution, the reaction temperature and the reaction time, it was found that when the acetic acid concentration was 5M and 7M, no obvious COF diffraction peak appeared, indicating that the COF structure was not formed under this condition; when the reaction temperature was 120°C and 170°C, the diffraction peaks all showed an amorphous structure, indicating that the COF structure was not formed under this condition; when the reaction time was 2 and 5 days, the diffraction peaks were relatively weak, especially the small-angle diffraction peaks were not obvious, indicating that the COF crystallinity was poor under this condition.

[0072] In this specification, the same or similar parts between the various embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. In particular, for the embodiments described later, the description is relatively simple, and the relevant parts can be referred to the partial description of the previous embodiments.

[0073] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of them with equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. Application of a tripolyindenone-based two-dimensional covalent organic framework material as a positive electrode material for lithium-ion batteries, characterized in that: The trimeric indenone-based two-dimensional covalent organic framework material has a structure as shown in formula (I):

2. The use according to claim 1, characterized in that: The tripolyindenone-based two-dimensional covalent organic framework material is mixed with conductive carbon and a binder in a mass ratio of 5:4:1 to prepare a positive electrode sheet.

3. The use according to claim 2, characterized in that: The matching negative electrode is a lithium sheet, and in the matching electrolyte, the organic solvent is composed of ethylene glycol dimethyl ether and 1,3-dioxolane in a volume ratio of 1:1, and the solute is lithium bis(trifluoromethanesulfonyl)imide with a concentration of 1 mol / L.

4. A trimeric indenone-based two-dimensional covalent organic framework material having a structure as shown in formula (I):

5. A method for preparing the tripolyindenone-based two-dimensional covalent organic framework material according to claim 4, characterized in that: The indanone-triamine and trimesic acid aldehyde are added to an organic solvent in a molar ratio of 1-5:1-5, and fully dispersed by ultrasound. Then an acidic catalyst is added, and then degassing is carried out by circulating liquid nitrogen freeze-vacuum-thaw, and then reacted at 130-160° C. for 3-4 days to obtain a suspension. After the suspension is cooled to room temperature, the precipitate is collected by filtration, and the indanone-based two-dimensional covalent organic framework material is obtained after multiple washing, purification and drying.

6. The preparation method according to claim 5, characterized in that: The organic solvent is one or more of mesitylene, 1,4-dioxane, toluene, chlorobenzene, pyridine and cyclohexanone.

7. The preparation method according to claim 6, characterized in that: The organic solvent is composed of mesitylene and 1,4-dioxane mixed in a volume ratio of 1:

1.

8. The preparation method according to claim 5, characterized in that: The acidic catalyst is one or more of acetic acid, trifluoroacetic acid, sulfuric acid and propionic acid.

9. The preparation method according to claim 8, characterized in that: The acidic catalyst is acetic acid with a concentration of 6 mol / L, and the volume ratio of acetic acid to organic solvent is 1:

10.

10. The preparation method according to claim 5, characterized in that: After degassing, the mixture was reacted at 150°C for 3 days to obtain a suspension.

Citation Information

Patent Citations

  • Heteroatom-containing covalent organic framework electrode material and preparation method and application thereof

    CN111682207A

  • Phenoxazine-based two-dimensional covalent organic framework material and preparation method and application thereof

    CN113754884A

  • Covalent organic framework material based on indanone skeleton as well as preparation method and application of covalent organic framework material

    CN114591476A

  • High-capacity conjugated multi-carbonyl organic electrode material and preparation method and application thereof

    CN117624599A

  • Method for the synthesis of covalent organic frameworks

    WO2015015035A1